3-(1H-benzoimidazol-2-yl)-chromen-2-ylideneamine platinum(II) and ruthenium(II) complexes exert their high in vitro antitumor activity by inducing S-phase arrest and disrupting mitochondrial functions in SK-OV-3/DDP tumor cells. (1st January 2019) - Qin, Qi-Pin; Wang, Shu-Long; Tan, Ming-Xiong; Luo, Dong-Mei; Wang, Zhen-Feng; Wei, Qing-Min; Wu, Xue-Yu; Zou, Bi-Qun; Liu, Yan-Cheng
Graphical abstract: Pt(II) complex1- induced mitochondrial dysfunction could be an valuable target for the development of new anticancer drugs. Abstract: Two new Pt(II) and Ru(II) complexes, [Pt(BFCY)Cl2 ] (1 ) and [RuCl2 (BMCY)(DMSO)] (2 ) with 3-(1H-benzoimidazol-2-yl)-8-fluoro-chromen-2-ylideneamine (BFCY) and 3-(1H-benzoimidazol-2-yl)-8-methyl-chromen-2-ylideneamine (BMCY), were synthesized. The BFCY Pt(II) complex1 adopted an approximately four-coordinated square planar geometry, while BMCY complex2 formed a distorted octahedral geometry. Among the seven selected human cancer cell lines, the two new Pt(II) and Ru(II) complexes1 and2 exhibited more potent activities against cisplatin-resistant SK-OV-3/DDP tumor cells (IC50  = 2.08 ± 1.04 μM and 18.06 ± 0.36 μM, respectively), compared with the free BFCY and BMCY ligands as well as cisplatin. In addition, the BFCY Pt(II) complex1 could induce cell cycle arrest in S phase and regulate the S-phase cell cycle-related proteins. Remarkably, the BFCY Pt(II) complex1 also induced mitochondrial dysfunction.